Fine mapping of the genetic locus L1 conferring black pods using a chromosome segment substitution line population of soybean. Issue 4 (25th May 2015) - He, Qingyuan; Yang, Hongyan; Xiang, Shihua; Tian, Dong; Wang, Wubin; Zhao, Tuanjie; Gai, Junyi; Singh, R.
Abstract The colour of plant organs is a useful trait in crop breeding. The pod colours of soybeans primarily include black, brown and tan types, which are controlled by two classical genetic loci, L1 and L2. Most wild soybeans have black pods, which reflect a possible role in adaptation to the natural environment. Here, an improved chromosome segment substitution line (CSSL) population SojaCSSLP3 was established to identify the L1 gene. The segment on the 19th chromosome represented by the SSR marker Satt313 was found to link with locus L1. The region was further delimited three times with increased SSR and InDel markers using a population derived from a heterozygous plant of CSSL124 from SojaCSSLP3. The L1 gene was finally located in a 184.43‐kb region between SSR_19p09 and Indel_19P7. Thirteen putative genes in this region were analysed with qRT‐PCR. The expression level of Glyma19 g27460, which is a member of the SANT superfamily with a MYB DNA‐binding domain, was significantly upregulated in black pods and was recognized to be the most likely candidate for the L1 gene.